Russia’s “soft power” impact in the field of educational migration (Journal of Philosophy Culture and Political Science, 2021)
The article is devoted to the study of the of Russia‘s “soft power” on the process of educational migration.The concept of “soft power”, formulated by neoliberalism theorists, is a reflection of the desire ofworld powers, including Russia, for geopolitical influence through the spread of education, culture andlanguage. The relevance of this article is due to the fact that the Russian vector of educational migrationis one of the main ones for Kazakhstani youth; according to statistics, in the 2019/2020 academic year,more than 70 thousand Kazakhstani students studied at various higher educational institutions in Russia.The article deals with such issues as the potential of Russian education for positioning in the internationalmarket of educational services; the demographic situation that stimulates migration processes, as well asthe main objectives of the state policy of the Russian Federation to attract educational migrants. Comprehensivestudy and analysis of all aspects of educational migration to Russia is an important appliedtask for modeling and predicting the consequences of migration of students from Kazakhstan, planningissues of educational, cultural, scientific and humanitarian cooperation between the Russian Federationand Kazakhstan in General. This article was prepared in the framework of the MES project “Educationalmigration from Kazakhstan: trends, factors and socio-political consequences”.Key words: «soft power», educational migration, state policy, export of educational services, demographicfactors, educational migration from Kazakhstan.